PENGEMBANGAN SISTEM ADMINISTRASI PENGELOLAAN PENJUALAN DAN PRODUKSI SECARA TERINTEGRASI BERBASIS WEBSITE - Christopher David Rolophan Pakpahan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Sales administration has an important role as a liaison between customers and companies in selling an item. But over time, the application of technology has become an important key in managing sales and production in a company. There are still many companies that use the sales and production system manually (noted), which makes the company less efficient so that it is detrimental to the company. Therefore, a website is made that is integrated with the sales and production administration system using the prototype method. Website obtained from analysis of customer problems, as well as system and application design. Based on the analysis of user satisfaction, the results obtained with satisfactory satisfaction 3.8, so that the system and website are suitable for use by the company. This website is expected to help companies manage sales and production, simplify management and reduce human errors. So that the company does not suffer losses caused by negligence from manual work when running a business within the company.